Implementasi Condition Based Maintenance (CBM) Pada Mesin Pasah Kayu Modern Terhadap Peningkatan Kualitas Produk Furniture Di UD Mitra Usaha Ngunut Tulungagung - Saputra , Muhammad Rizki Wahyu; Mahariani, Yeni Roha (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
Small and medium-sized furniture industries rely heavily on the reliability of production machinery to maintain consistent product quality and ensure smooth manufacturing processes. However, maintenance practices in the SME sector are still predominantly reactive, which can increase downtime, reduce product quality, and accelerate component wear. This study aims to analyze the implementation of Condition-Based Maintenance (CBM) on modern wood planing machines at UD Mitra Usaha Ngunut, Tulungagung, through monitoring of temperature, vibration, and noise parameters. A case study approach was employed using observation, interviews, and documentation analysis. The results indicate that CBM implementation significantly extended component service life, as evidenced by an increase in planer blade lifespan from an average of 6 months to 8–9 months (33–50%), carbon brush lifespan by 25–30%, and armature, bearing, and fan belt lifespan by 20–40%, depending on operating conditions. In addition, CBM reduced average operating temperature by 8–12%, decreased vibration intensity by up to 30%, and maintained noise levels within safe limits. CBM implementation was also shown to reduce production downtime by up to 35% and improve maintenance cost efficiency. These findings demonstrate that CBM is effective in enhancing machine reliability and furniture product quality in small and medium-sized industries.